2016
DOI: 10.1088/1674-1056/25/2/020101
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of robustness of urban bus network

Abstract: In this paper, the invulnerability and cascade failures are discussed for the urban bus network. Firstly, three static models(bus stop network, bus transfer network, and bus line network) are used to analyse the structure and invulnerability of urban bus network in order to understand the features of bus network comprehensively. Secondly, a new way is proposed to study the invulnerability of urban bus network by modelling two layered networks, i.e., the bus stop-line network and the bus line-transfer network a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…In Figure 3, we show an example for a DEG-based attack to a network. Some of the studies [76,77] only evaluate DEG of nodes for designing a targeted attack, e.g., stating that "for the selective attack strategy, we remove some nodes with higher degrees according to their degree order from high to low" [77]. Others compare a set of few static network metrics, but without considering interactive/iterative/dynamic metrics sufficiently for much stronger attacks [26,[78][79][80][81][82] (see Section 4.2 for further discussion).…”
Section: Common Pitfalls and Misleading Interpretationsmentioning
confidence: 99%
“…In Figure 3, we show an example for a DEG-based attack to a network. Some of the studies [76,77] only evaluate DEG of nodes for designing a targeted attack, e.g., stating that "for the selective attack strategy, we remove some nodes with higher degrees according to their degree order from high to low" [77]. Others compare a set of few static network metrics, but without considering interactive/iterative/dynamic metrics sufficiently for much stronger attacks [26,[78][79][80][81][82] (see Section 4.2 for further discussion).…”
Section: Common Pitfalls and Misleading Interpretationsmentioning
confidence: 99%
“…Diffusion weighted imaging (DWI) has been applied to diagnosis of diseases, including HAE, in abdominal organs [ 6 9 ]. In a comparative study between DWI and histopathological features of HAE, Ren et al, found a significant negative correlation between apparent diffusion coefficient (ADC) values and percentage of HAE fibrosis in the peripheral area [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion weighted imaging (DWI) has been applied to diagnosis of diseases, including HAE, in abdominal organs [ 6 9 ]. In a comparative study between DWI and histopathological features of HAE, Ren et al, found a significant negative correlation between apparent diffusion coefficient (ADC) values and percentage of HAE fibrosis in the peripheral area [ 9 ]. In recent years, intravoxel incoherent motion diffusion weighted magnetic resonance imaging (IVIM DW MRI), which was first described by Le Bihan et al [ 10 ], has been applied in the clinical diagnosis of HAE.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction. Complex network are widely used in the real world, like music field [11], urban transport field [12]. In recent years, a variety of online social networks grow rapidly, such as Facebook, weibo and WeChat [17].…”
mentioning
confidence: 99%